Tratamento com corrente interferencial reduz a dor lombar e melhora a funcionalidade em pacientes com lombalgia crônica - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Low back pain is characterized by pain and represents a change in health that mainly affects adults, although electrostimulation represents an important tool in the treatment of patients with chronic nonspecific low back pain, the clinical efficacy of the interferential current used in physiotherapy still lacks reinforcement for clinical validation. Thus, in the present study, we evaluated whether the use of interferential current contributes to reducing chronic low back pain and analyzed whether the electrotherapeutic protocol can benefit the physical functionality of patients with chronic low back pain. 24 individuals were evaluated, with low back pain for more than 12 weeks and aged between 12 and 65 years. The current used in the lumbar region of the participants was of the tetrapolar interferential type and the stimulation mode was automatic vector, carrier frequency of 4,000 Hz, modulation frequency (AMF) of 50 Hz, SWEEP frequency of 20Hz. Pain and functionality assessment were performed using the data collection instrument the Visual Analog Pain Scale (VAS), Rolland Morris Disability Questionnaire (RMDQ) and the Owestry Disability Questionnaire (ODQ) respectively. Data analysis was performed using the JAMOVI 2.2.5 software. Our data demonstrate that individuals submitted to interferential current present significant improvement in pain relief, as well as in the functional pattern, opening new perspectives on the use of this therapeutic approach.
Keywords: Qualidade de vida; Doença Ocupacional; Funcionalidade Física; Ciências da Saúde